Features of Belarusian travel series as a hybrid genre (rhetorical assumption) - Morozowa, Elena I. (Journal of the Belarusian State University. Journalism, 2021)
In the article popular in convergent media genre of travel series is investigated on the basis of a wide historical material of Belarusian television programmes, from 1956 to the present, which allows to show it as a hybrid genre that develops at the intersection of socio-political information, drama, documentary, and also consumer information and reality (from middle 1980s). Shift of the semantic centre of the genre release from the author to the characters and then to the viewer,that started from 1970s, has been determined. Within the framework of the programme «Wind of wanderings», the formation of a stable audience of travel issues which is the young Belarusian scientific and technical intelligentsia is shown. The article reveals the peculiarities that make it possible to call the travel release of the Belarusian television a harbinger of the national blog.
Keywords: travel series; rhetorical assumption; rhetorical strategies; means and techniques of artistic expression; hybrid genre